Regime of international public-private partnership to intensify cooperation between Ukraine and Poland in science, technology and innovation spheres - Liashenko, Viacheslav; Petrova, Iryna (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
The European experience of PPP in scientific, technical and innovative spheres is analyzed. It is determined that the role of the state is to promote the development of fundamental knowledge and complex technologies of strategic nature, creating infrastructure and a favorable climate for innovation, and business - in creating technologies based on their own research and market development of innovations. It is proposed to introduce a regime of international public-private partnership to intensify cooperation between Ukraine and Poland in the scientific, technical and innovation spheres. The components of the regime of international public-private partnership are considered. It is determined that the regime of international public-private partnership will allow to establish participation between international financial institutions, public authorities, higher education institutions / research institutions and business in joint financing of projects in scientific, technical and innovative activities of Ukraine and Poland.